Use of Renal Replacement Therapy in a Neonatal Foal with Postresuscitation Acute Renal Failure. (12th February 2017) - Wong, D.M.; Ruby, R.E.; Eatroff, A.; Yaeger, M.J.
Abstract : A newborn foal was presented because it was unresponsive and in cardiopulmonary arrest. Aggressive cardiopulmonary cerebral resuscitation was administered to the foal, which revived the foal; however, acute renal failure developed. Fluid retention and azotemia occurred although the foal was alert and able to suckle. A 6‐hour renal replacement therapy session using hemodiafiltration and a continuous renal replacement therapy machine was administered to the foal at 3 days of age which lowered the foal's azotemia and facilitated removal of some of the excess body fluid. Despite therapy, the foal developed pulmonary edema and was euthanized. Although the foal in this case did not survive, this report highlights the possibility of developing postresuscitation complications such as acute renal failure and describes the use of renal replacement therapy using hemodiafiltration as a viable option in neonatal foals with acute kidney injury.